THE DOMESTIC VIOLENCE AGAINST AFGHAN WOMEN IN ATIQ RAHIMI’S THE PATIENCE STONE: A FEMINIST NEW HISTORICISM READING - Dyah Rochmawati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2014)
Domestic violence is physical, psychological, sexual or financial violence that takes place within an intimate or family-type relationship and forms a pattern of coercive and controlling behavior. It is very common: research shows that it affects one in four women in their lifetime. Two women a week are killed by their partners or former partners. All forms of domestic violence - psychological, financial, emotional and physical - come from the abuser's desire for power and control over an intimate partner or other family members. Domestic violence is repetitive and life-threatening, it tends to worsen over time and it destroys the lives of women and children. Domestic violence has long been common in Afghanistan as depicted in Atiq Rahimi’s Patience Stone. The present article discusses the domestic violence against Afghan Women in the novel through the lenses of feminism and new historicism. It is also combined with Rabrindranath Tagore’s conception on woman.